A miniature tooth-borne distractor for the alignment of ankylosed teeth - (:unkn) unknown (My University, 2006)
The ankylosis of a tooth is one of the most difficult clinical problems that an orthodontist faces. In the literature, the treatment protocols for ankylosed teeth are still insufficient and questionable when considering gingival esthetics and conservation of bone health. The purpose of this report is to evaluate and discuss the effects of a newly designed miniature tooth distractor (MTD), which can be used with infrapositioned ankylosed teeth. Two cases with vertically malpositioned incisors were treated using the MTD, and this device was evaluated and compared with the distraction appliances used before in the literature. In conclusion, it was found to be efficient with its small dimensions, ease of application and removal, ease of activation, buccolingual control, and patient tolerance.
Keywords: Female; Humans; Adolescent; Male; Orthodontics, Corrective; Incisor; Osteogenesis, Distraction; Tooth Ankylosis